The temptation and downfall of the Vicar of Stanton Lacy : being the story of Robert Foulkes, the late vicar of the parish of Stanton Lacy near Ludlow, in Shropshire who was tried, convicted, and sentenced for murder at the Sessions House in the Old Bailey, London on January 16th 1679, and executed on the 31st following /: being the story of Robert Foulkes, the late vicar of the parish of Stanton Lacy near Ludlow, in Shropshire who was tried, convicted, and sentenced for murder at the Sessions House in the Old Bailey, London on January 16th 1679, and executed on the 31st following. (2017) - Unknown
No abstract available